A Harmonic Suppression Rectifier Transformer with Filters for an Industrial Rectifier System - Li, Jianying; Luo, Longfu; Xu, Jiazhu (Recent Advances in Electrical & Electronic Engineering, 2014)
This paper presents a new harmonic suppression rectifier transformer with filters and a transformer filtering technology to improve power quality of industrial rectifier system. According to the special circuit topology of the new rectifier transformer, the current relationship is deduced between the grid side and valve side windings, along with the valve side and filtering windings, and the implementation conditions of the transformer filtering technology are described. Then, the harmonic transfer mathematic model is established to analyze the effects of filters on harmonic transfer characteristics, and the relationship between the grid side voltage and current is deduced to analyze the reactive power compensation characteristics. Theoretical analysis shows that the transformer filtering technology can prevent the harmonic currents from flowing into the primary winding of the new rectifier transformer and the reactive power can be partly compensated in the secondary winding, which means that the effects of the harmonic and reactive currents on the transformer can be greatly reduced. Finally, the experimental results verify the correctness of the theoretical analysis and calculation.
Keywords: full-tuned filters